ESTUDO COMPARATIVO ENTRE MÉTODOS DE DETECÇÃO DA FALHAS EM SISTEMAS DE DISTRIBUIÇÃO DE ENERGIA - Campos, Maurício d.; Sausen, Paulo S.; Padoin, Édson L.; Dill, Sérgio L.; Salvadori, Fabiano; Schonardie, Mateus (Salão do Conhecimento, 2013)
Resumo